Checklist of the marine bivalves from Peru - Paredes, Carlos (2016)
A checklist of the marine bivalve species from Peru is presented, this list has 401 species which are distributed in 65 families and 195 genera. The taxonomical classification and nomenclature is based on classical and current bibliography including Bernard (1983) and Coan & Valentich-Scott (2012). We give distribution and hábitat information about every species.